High levels of genetic differentiation and selfing in the Brazilian cerrado fruit tree Dipteryx alata Vog. (Fabaceae) - Tarazi, Roberto; Moreno, Maria Andréia; Gandara, Flávio Bertin; Ferraz, Elza Martins; Moraes, Mário Luiz Teixeira [UNESP]; Vinson, Christina Cleo; Ciampi, Ana Yamaguishi; Vencovsky, Roland; Kageyama, Paulo Yoshio (FapUNIFESP (SciELO), 2010)
Dipteryx alatais a native fruit tree species of the cerrado (Brazilian savanna) that has great economic potential because of its multiple uses. Knowledge of how the genetic variability of this species is organized within and among populations would be useful for genetic conservation and breeding programs. We used nine simple sequence repeat (SSR) primers developed for Dipteryx odoratato evaluate the genetic structure of three populations of D. alatalocated in central Brazil based on a leaf sample analysis from 101 adults. The outcrossing rate was evaluated using 300 open-pollinated offspring from 25 seed-trees. Pollen dispersal was measured by parentage analysis. We used spatial genetic structure (SGS) to test the minimal distance for harvesting seeds in conservation and breeding programs. Our data indicate that the populations studied had a high degree of genetic diversity (Ĥe =0.619) and population structure, as suggested by the high level of divergence among populations (ĜST =0.803). The estimated outcrossing rate (t̂m =0.711) suggested a mixed mating system, and the intrapopulation fixation index was influenced by SGS. We conclude that seed harvesting for genetic conservation and breeding programs requires a minimum distance between trees of 196 m to avoid collecting seeds from related seed-trees. Copyright © 2009, Sociedade Brasileira de Genética.
Keywords: Dipteryx alata; Genetic structure; Mating system; SSR